2003
DOI: 10.1080/02678290310001601996
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation spectroscopy of a nematic liquid crystal doped with ferroelectric Sn 2 P 2 S 6 nanoparticles

Abstract: To cite this article: E. Ouskova , O. Buchnev , V. Reshetnyak , Yu. Reznikov & H. Kresse (2003) Dielectric relaxation spectroscopy of a nematic liquid crystal doped with ferroelectric Sn 2 P 2 S 6 nanoparticles, Liquid Crystals, 30:10, It was found that doping a nematic liquid crystal (LC) with a small amount of ferroelectric nanoparticles strongly affects the dielectric properties of the system. In particular, adding the ferroelectric particles results in a shift of the absorption bands corresponding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 9 publications
2
78
0
4
Order By: Relevance
“…One particularly interesting case occurs if the particles are ferroelectric. Experiments have shown that low concentrations of ferroelectric Sn 2 P 2 S 6 or BaTiO 3 nanoparticles increase the orientational order parameter, increase the isotropic-nematic transition temperature, and decrease the switching voltage for the Frederiks transition [7][8][9][10][11][12][13][14]. Thus, they provide a new opportunity to enhance the properties of liquid crystals for technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…One particularly interesting case occurs if the particles are ferroelectric. Experiments have shown that low concentrations of ferroelectric Sn 2 P 2 S 6 or BaTiO 3 nanoparticles increase the orientational order parameter, increase the isotropic-nematic transition temperature, and decrease the switching voltage for the Frederiks transition [7][8][9][10][11][12][13][14]. Thus, they provide a new opportunity to enhance the properties of liquid crystals for technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus one can readily see (compare also with Figs. 3a and 3b) that the experimentally observed increase of the dielectric constant [9,13] at very low NP number density ρ = 10 −2 − 10 −3 can be explained by the effect of chain formation only if the dipole-dipole interaction strength is sufficiently high which is the case for ferroelectric NPs with large spontaneous polarization.…”
Section: B Low-frequency Dielectric Anisotropymentioning
confidence: 99%
“…Strongly anisotropic interaction between NPs, including, in particular, the dipole-dipole one, will lead to the formation of polar chains. It has been shown [13] that the equilibrium chain length strongly depends on the contact interaction potential normalized by the temperature. Long chains of NPs may occur only if the contact interaction is of the order of 10k B T [15] which is satisfied, for example, for ferroelectric NPs [9,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…carbon nanotubes, silica microbeads, nanoparticles and various collides exhibit remarkable new physical phenomena. Experiments have shown that nanoparticles and ferroelectric nanoparticles can greatly enhance the physical properties of nematic and smectic liquid crystals [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%